Pengaruh Brand Sensory Experience, Brand Cognitive Experience dan Perceived Behavioral Control melalui Attitude Toward Behavior dan Subjective Norm - Rindi Rahmawati; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of brand sensory experience and brand cognitive experience on repurchase intention through attitude toward behavior and subjective norms, as well as the influence of perceived behavioral control on repurchase intention, both directly and through attitude toward behavior, among consumers of 600 ml bottled AMDK Club in Cimahi City. The research method used a quantitative survey approach, using a questionnaire as a data collection tool. The study sample consisted of 130 respondents selected using a purposive sampling technique, with the criteria of having consumed AMDK Club at least five times and being at least 17 years old. Data analysis was performed using variance-based Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.0 software. The results showed that brand sensory experience had a positive effect on subjective norms and attitudes toward behavior, and an indirect effect on repurchase intention through these two variables. Brand cognitive experience had a positive effect on subjective norms and an indirect effect on repurchase intention through subjective norms, but not through attitudes toward behavior. Furthermore, perceived behavioral control has a positive influence on attitudes toward the behavior and repurchase intentions, as well as an indirect influence on repurchase intentions through attitudes toward the behavior. The conclusion of this study is that AMDK Club consumers' repurchase intentions are significantly influenced by sensory and cognitive brand experiences through psychological mechanisms within the Theory of Planned Behavior framework. Therefore, brand experience enhancement and ease of consumption are important factors in increasing consumer repurchase intentions. Keywords: Brand Sensory Experience, Brand Cognitive Experience, Perceived Behavioral Control, Repurchase Intention, Theory of Planned Behavior